Single Cell Protein Production through Multi Food-Waste Substrate Fermentation - Tropea, Alessia; Ferracane, Antonio; Albergamo, Ambrogina; Potortì, Angela Giorgia; Lo Turco, Vincenzo; Di Bella, Giuseppa (Fermentation (Basel), 2022)
Today, food valorization represents an important challenge to environmental sustainability. Food waste can be used as a substrate for single cell protein production suitable for animal feed. In this study, animal and agricultural food waste, represented by fish, pineapple, banana, apple, and citrus peels, have been used simultaneously as a fermentation substrate for single cell protein production by Saccharomyces cerevisiae, to evaluate the possibility of using a multi complex substrate for a simultaneous biovalorization of different food waste. The fermentation process was implemented by the supplementation of a hydrolytic enzyme and nutrient to allow the best yeast growing conditions. At the end of the process, the final substrate was enriched in protein, reaching up to 40.19% of protein, making the multisubstrate useful for animal feed. The substrate was also investigated for crude lipid, ash, lignin, soluble and insoluble sugar. The substrate composition at the end of the fermentation process was represented by 14.46% of crude lipid, 1.08% ash, 6.29% lignin. Conversely, the soluble and insoluble sugars dropped down from 20.5% to 6.10% and 19.15% to 2.14%, respectively, at the end of the process.